Microcephaly and Zika virus: neonatal neuroradiological aspects - Cavalheiro, Sergio (Childs Nerv Syst, 2016)
PURPOSE: The aim of this study is to describe some radiological features in the newborns with microcephaly caused by Zika virus infection during pregnancy. METHODS: We radiologically analyzed 13 cases of newborns with microcephaly born to mothers who were infected by the Zika virus in the early stage of pregnancy. RESULTS: The most frequently observed radiological findings were microcephaly and decreased brain parenchymal volume associated with lissencephaly, ventriculomegaly secondary to the lack of brain tissue (not hypertensive), and coarse and anarchic calcifications mainly involving the subcortical cortical transition, and the basal ganglia. CONCLUSIONS: Although it cannot be concluded that there is a definitive pathognomonic radiographic pattern of microcephaly caused by Zika virus, gross calcifications and anarchic distribution involving the subcortical cortical transition and the basal ganglia, in association with lissencephaly and in the absence of hypertensive ventriculomegaly, are characteristic of this type of infection.